Psychological Policy For Women: A Strategy Towards Gender Equity in Indonesia - Indriastuti; Suprayoga; Dwi Hardaningtyas (Universitas Muhammadiyah Jember Press, 2025)
Women in Indonesia face high vulnerability to mental health problems due to gender inequality, gender-based violence, and a lack of gender-responsive psychological services. This study aims to analyze existing psychological policies and evaluate their impact on gender equity. Using a literature review approach of policy documents, scientific journals, and national and international reports from the last five years (2020–2025), it was found that the integration of a gender perspective in mental health services remains limited. Lack of training for mental health workers, weak coordination between sectors, and suboptimal community-based advocacy are key obstacles. Evidence-based policy reform, increasing human resource capacity, and strengthening women's roles in policy processes are important strategies towards gender equity in mental health